Laparoscopic versus open liver resection for hepatocellular carcinoma in elderly patients: a propensity score matching analysis. Issue 6 (June 2022) - Delvecchio, Antonella; Conticchio, Maria; Riccelli, Umberto; Ferraro, Valentina; Ratti, Francesca; Gelli, Maximiliano; Anelli, Ferdinando M.; Laurent, Alexis; Vitali, Giulio C.; Magistri, Paolo; Assirati, Giacomo; Felli, Emanuele; et al.
Abstract: Background: Surgical resection is a first-line curative option for hepatocellular carcinoma, but its role is still unclear in elderly patients. The aim of our study was to compare short- and long-term outcomes of laparoscopic and open liver resection in elderly patients with hepatocellular carcinoma. Methods: The study included 665 consecutive hepatocellular carcinoma liver resection cases in patients with ≥70 years of age treated in eight European hospital centres. Patients were divided into laparoscopic and open liver resection groups. Perioperative and long-term outcomes were compared between these groups. Results: After a 1:1 propensity score matching, 219 patients were included in each group. Clavien-Dindo grades III/IV (6 vs. 20%, p = 0.04) were lower in the laparoscopic than in the open matched group. Hospital stay was shorter in the laparoscopic than in the open matched group (5 vs. 7 days, p < 0.001). There were no significant differences between laparoscopic and open groups regarding overall survival and disease-free survival at 1-, 3- and 5- year periods. Conclusion: Laparoscopic liver resection for hepatocellular carcinoma is associated with good short-term outcomes in patients with ≥70 years of age compared to open liver resection. Laparoscopic liver resection is safe and feasible in elderly patients with hepatocellular carcinoma. Graphical abstract: Image 1